Peranan Guru Sekolah Minggu dalam Membangun Budaya Membaca dan Menulis - Ferry Yeferson Tulle (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2021)
Reading and writing is the first commandment that was revealed by God to humans, It is an encouragement to mankind to read meaningful books and books of life about successful characters both in the Bible and who are currently the owners of Science (written on natural events) through reading here's gonna be know. Living in an oral culture from year to year, unable to manage a reading and writing culture. It should be realized that making a personal library at home. Has the house held many books of knowledge for children? Children who are students and students, because books are knowledge that must be added to in order to get clear water of knowledge. The tradition of reading which has now been widely practiced in the world of formal education should also be cultivated wherever and whenever. Make books a good friend, at church at school or wherever we are. every month the money is set aside to buy books to save for children, so that children do not bother when children study at school, smart children answer questions from teachers at school can excel through reading, reading and writing.